Identification of pathogenic bacteria isolated from raw and after sand filtration water at Lubok Buntar Water Treatment Plant / Nur Hafizah Zakaria …[et al.] - Zakaria, Nur Hafizah; Tajarudin, Husnul Azan; Mohd Sapingi, Mohd Sharizal; Murshed, Mohamad Fared (Universiti Teknologi MARA Shah Alam, 2017)
This study focused on the identification of pathogenic bacteria in raw water intake and after sand filtration for drinking water treatment plant during flood event in 2014. The samples was collected from the Lubok Buntar Water Treatment Plant (WTP) and processed through bacterial isolation using chocolate agar as a media. The isolation process conducted based on serial samples dilution and streaking method prior to DNA extraction. Deoxyribonucleic acid (DNA) extraction kit was used to get selected bacteria DNA and further analysis using Polymerase Chain Reaction (PCR) test and electrophoresis to get DNA sequences. The Basic Local Alignment Search Tool (BLAST) analysis was employed to identify the species of the isolated bacteria. As a result, Pantoeaagglomerans and Enterobacter sp. were found in raw and filtered water sample and indicating the same family types. It was concluded that bacteria of the same species were found before and after sand filtration and need to be removed by disinfectant process. The findings also indicated that all the physicochemical parameters measured were within the values prescribed by the Interim National Water Quality Standard (INWQS).